2023
DOI: 10.3390/diseases11040138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics in Adults with Gastroenteritis: A Systematic Review and Meta-Analysis of Clinical Trials

Amal K. Mitra,
Adetoun F. Asala,
Shelia Malone
et al.

Abstract: Probiotics have been widely used in gastroenteritis due to acute and chronic illnesses. However, evidence supporting the effectiveness of probiotics in different health conditions is inconclusive and conflicting. The aim of this study was to review the existing literature on the effects of probiotics on gastroenteritis among adults. Only original articles on clinical trials that demonstrated the effects of probiotics in adults with gastroenteritis were used for this analysis. Multiple databases, such as PubMed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Zocco showed that the use of Lactobacillus rhamnosus GG alone or in combination with mesalazine prolonged the duration of clinical remission in UC patients at one-year follow-up, compared to patients treated with mesalazine alone. [18] [29] Preliminary studies have shown that non-pathogenic S. boulardii yeast was effectively used to induce and maintain remission in patients with mild to moderate UC.…”
Section: Probiotics and Colitis Ulcerosamentioning
confidence: 99%
“…Zocco showed that the use of Lactobacillus rhamnosus GG alone or in combination with mesalazine prolonged the duration of clinical remission in UC patients at one-year follow-up, compared to patients treated with mesalazine alone. [18] [29] Preliminary studies have shown that non-pathogenic S. boulardii yeast was effectively used to induce and maintain remission in patients with mild to moderate UC.…”
Section: Probiotics and Colitis Ulcerosamentioning
confidence: 99%
“…Worldwide, around 1.5 to 2.5 million children die each year from diarrhea and dehydration that is caused by gastroenteritis (Hartman et al, 2019). Additionally, 68% of diarrheal disease occurs in young children globally as well as it is reported as the fifth leading killer of young children (Mitra et al, 2023;Hartman et al, 2019). Gastroenteritis is an inflammation of the digestive tract that results in diarrhea, vomiting, or both, nausea, poor appetite, and other symptoms of digestive upset (abdominal cramps) could occur.…”
Section: Introductionmentioning
confidence: 99%
“…Severe gastroenteritis causes dehydration and electrolytes imbalance because of a loss of body fluids in the vomit and stool. Nearly three to five milliard episodes occur globally annually, most common in children under five years who habitat in countries where those children are more at risk, and often difficult to access care (Mitra et al, 2023;Hartman et al, 2019). According to the World Health Organization (WHO) dehydration is defined as a condition that results from excessive loss of body water.…”
Section: Introductionmentioning
confidence: 99%